Analisis Penerapan Sistem Informasi Akuntansi di Kantor Walikota Pematang Siantar - Harudini Nizar Situmorang; Arnida Wahyuni Lubis (BADAN PENERBIT STIEPARI PRESS, 2024)
The aim of this research is to study and understand how the Accounting Information System (AIS) is implemented at the Pematang Siantar City Hall. This research is included in the type of descriptive research using a qualitative approach. Researchers obtained research results, namely that the application of the accounting information system in the Pematang Siantar City Hall environment, including the use of the Regional Financial Management Information System (SIMDA), has been implemented but there are still several obstacles or constraints in the implementation process. The obstacles that researchers found were Human Resources (HR) which were still considered less reliable in operating the SIMDA Finance application, not yet integrated into all online Village Work Units (SKPD) and the absence of an Order (SK) from the Mayor of Pematang Siantar regarding the formation of a SIMDA financial management group. . From the research results, it can be concluded that the implementation of SIA in the form of a regional financial management information system (FIMS) is already underway, but there are several obstacles or limitations that need to be overcome so that it can be realized or implemented. Implementation of Financial SIMDA can run optimally and according to plan. Factors that support the implementation of SIMDA are communication, attitudes/predispositions, and bureaucratic structure. The slowing factor is human resources. The quality of information produced by SIMDA sponsors is understandable, relevant, reliable and comparable.